Dream and reality in the poetry of david gascoigne (linguistic analysis of the poem and the seventh dream is the dream of isis) - Pradivlianna, Liudmyla; Pradivlianna, L.; Прадивлянная, Людмила (ПП "Фенікс", 2018)
Сюрреалізм, літературний та мистецький рух початку ХХ століття, став об’єктом значної кількості наукових досліджень. Ця стаття вивчає сюрреалізм як тип художнього мислення, який підняв роль несвідомого в поезії, та зосереджується на центральному понятті сюрреалістичної естетики – автоматичному образі, який дозволив поетам вивчати ірраціональні стани. Орієнтуючись на дослідження сновидіння, сюрреалісти створили поезію, що наповнена специфічними образами, які, надходячи безпосередньо з несвідомого, несуть нові знання про світ та людей. Поет – лише провідник, тому саме читач повинен відшукати сенс цієї поезії. У статті розглядається сюрреалізм з точки зору лінгво-поетичного експерименту та аналізуються лінгвістичні характеристики автоматичних текстів у ранній поетичній збірці Девіда Гаскойна (1916-2001). Висвітлено особливості прийомів творчості британського поета, які побудовані на французьких сюрреалістичних концепціях і теоріях, а також розглянуто фонетичні, семантичні та синтаксичні аспекти його поезії. Тексти Девіда Гаскойна демонструють прихильність поета до французької версії сюрреалізму, його зацікавленість у несвідомому і сновидіннях. Потоки довільних візуальних образів, глибока емоційність, художнє використання слова, смислові прирости сенсу роблять тексти Гаскойна відкритими для інтерпретації. Поет надає перевагу створенню насамперед візуальних образів, використовуючи спеціальну лексику (ми бачимо сновидіння), але неповторна канва його лірики створюється не тільки лексичними, але й фонетичними повторами, через інтонацію, в якій лексеми набувають нове смислове навантаження.

Surrealism, the XX century literature and art movement, inspired an impressive number of scientific research regarding different aspects of the phenomenon. This paper studies surrealism as a type of artistic thinking which raised the role of the unconscious in poetry. It focuses on the core of surrealist aesthetics – an automatic image, which allowed the poets to study human irrational states, such as dreams. Focusing on the themes of dreams and dream-like narrations, surrealists created poetry which was formed by specific images. An automatic image coming directly from one’s unconscious mind was expected to reveal new knowledge about the world and people. But as the poet ’functions’ only as a conductor of the unconscious images, it is the reader who has to create meanings in this kind of poetry.The paper regards surrealism in terms of a lingvo-poetic experiment and analyzes the linguistic characteristics of the automatic texts in the early poetic collection of David Gascoyne (1916–2001). It outlines the peculiarities of the British poet’s techniques which are built upon French surrealist concepts and theories and examines phonetic, semantic and syntactic aspects of his poetry. David Gascoyne’s lyrics demonstrates the poet’s commitment to the French version of surrealism, his interest in the unconscious and dream-like narration. The streams of arbitrary visual images, deep emotionality, the artistic use of the word, semantic increments of meaning make Gascoigne’s texts open to interpretation. And though the poet actually prefers visual effects (we rather see dreams), specific dream-like patterns are created not only by lexical, but also by phonetic repetitions, via intonation in which lexemes acquire a new semantic load.
Pradivlianna, Liudmyla. Dream and reality in the poetry of david gascoigne (linguistic analysis of the poem and the seventh dream is the dream of isis) / L. Pradivlianna // Одеський лінгвістичний вісник. – 2018. – Вип. 12. – С. 32-38. DOI 10.32837/2312-3192/12/5
Keywords: Research Subject Categories::HUMANITIES and RELIGION; Сюрреалізм; Андре Бретон; сновидіння; автоматичне письмо; сюрреалістичний образ; Surrealism; André Breton; automatic writing; dream-like narration; David Gascoyne; surrealist image